The roles of Magnaporthe oryzae avirulence effectors involved in blast resistance/susceptibility - Liu, Xin; Hu, Xiaochun; Tu, Zhouyi; Sun, Zhenbiao; Qin, Peng; Liu, Yikang; Chen, Xinwei; Li, Zhiqiang; Jiang, Nan; Yang, Yuanzhu (Frontiers in Plant Science, 2024)
Phytopathogens represent an ongoing threat to crop production and a significant impediment to global food security. During the infection process, these pathogens spatiotemporally deploy a large array of effectors to sabotage host defense machinery and/or manipulate cellular pathways, thereby facilitating colonization and infection.However, besides their pivotal roles in pathogenesis, certain effectors, known as avirulence (AVR) effectors, can be directly or indirectly perceived by plant resistance (R) proteins, leading to race-specific resistance. An in-depth understanding of the intricate AVR-R interactions is instrumental for genetic improvement of crops and safeguarding them from diseases. Magnaporthe oryzae (M. oryzae), the causative agent of rice blast disease, is an exceptionally virulent and devastating fungal pathogen that induces blast disease on over 50 monocot plant species, including economically important crops. Rice-M. oryzae pathosystem serves as a prime model for functional dissection of AVR effectors and their interactions with R proteins and other target proteins in rice due to its scientific advantages and economic importance.Significant progress has been made in elucidating the potential roles of AVR effectors in the interaction between rice and M. oryzae over the past two decades. This review comprehensively discusses recent advancements in the field of M. oryzae AVR effectors, with a specific focus on their multifaceted roles through interactions with corresponding R/target proteins in rice during infection. Furthermore, we deliberated on the emerging strategies for engineering R proteins by leveraging the structural insights gained from M. oryzae AVR effectors.